Eukaryotic DNA does not form nucleosomes as readily as some prokaryotic DNA. - Getts, R C (1991)
Nucleosomal-length DNA was prepared from the genomic DNA of various prokaryotic and eukaryotic organisms by limited nuclease digestion after reconstitution with core histones. The DNAs ranged in base composition from 26.5% to 72% guanosine-plus-cytosine (%GC). The nucleosomal-length DNAs were then used in a competitive reconstitution assay in order to quantitatively determine their relative abilities to form nucleosomes. The results of the assay indicate a linear dependence of the free energy of nucleosome formation on base composition and, surprisingly, show that several prokaryotic DNAs form nucleosomes as well as or better than eukaryotic DNAs.